Implementasi Keadilan Restoratif Oleh Polri Dalam Penyelesaian Perkara Tindak Pidana Penganiayaan - Grace; Rahman Amin; Novega, Lidya (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2026)
The Indonesia National Police as a state tool in the field of security and public order, one of itsmain tasks is criminal law enforcement, where in the process of investigating criminal acts,Police Investigators can apply restorative justice in the settlement of criminal acts that occur.However, in reality, the application of restorative justice has not fully considered material andformal requirements with an emphasis on the recovery of victims of crimes. This research is anormative legal researcher, with a legislative approach and a case approach. The results of theresearch are, First, the provisions on restorative justice by the National Police in the settlementof criminal cases of persecution are regulated in the Regulation of the National Police ChiefNumber 6 of 2019 concerning Criminal Investigation and the National Police Regulation Number8 of 2021 concerning the Handling of Crimes Based on Restorative Justice, which regulates thematerial requirements and formal requirements that must be met in the application of restorativejustice. Second, the implementation of restorative justice by the National Police in the settlementof criminal cases of persecution in cases handled by the Investigator criminal investigation unitof the Bekasi City Metro Police, where the Investigator has resolved the case involving theperpetrator of CK and the victim of ID through restorative justice with the consideration thatthere has been a peace agreement and the provision of compensation from the perpetrator tothe victim, but the Investigator has not considered the material and other formal requirementsbetween does not cause public unrest, and the limiting principle is that the level of theperpetrator's fault is relatively not severe, and there is a need for an apology from theperpetrator to the victim and the community as a form of responsibility for the perpetrator inorder to restore a peaceful and peaceful situation as it was before the crime occurred